Comportamento fisiológico e produtividade de cafeeiro arábica - cultivar topázio MG 1190 - sob diferentes orientações cardeais - Bicalho, Grécia Oiama Dolabela (2007)
The coffee plant study of phenological development and productivity using TOPAZIO MG 1190 variety, was realized in different cardinal directions (N-S, NE- SW, E-W, and SE-NW) in the region of Patrocínio, Minas Gerais. The evaluations were initiated in October/2002, when the plants were two years old and, since this time, every month, on the both side of plants transversal of the sowing line, facing adjacent towpath. The experimental unit was made up of five rows containing15 plants, four consecutive plants of the three central rows were considered as the useful plot. The plant growth analysis was made in the four sowing line directions, and did not show significant differences, altough the seasonal growth pattern had accentuated growth rates in the spring/summer, combined with a period of slow growth in the fall/winter. The physiological analyses of gaseous exchanges and water potential also revealed no differences among the treatments, once the crop was under radiation conditions at saturated levels; and the temperature in the appropriate range, without water stress during the whole year. In relation to the production, the sum of the first three crops did not show differences among the row positins and neither in relation to the sides of the plant facing the towpath, taking into account the solar path. Considering all those aspects, it is possible to conclude that were neither reductions nor physiological aspects favoring for any directioning of the rows. Therefore, from the phenologic and productive point of view, the coffee grower of this area, according to his convenience, has the possibility of choosing the direction of the coffee lines in relation to the cardinal orientations without compromising his production.